Estimates for the best approximation and integral modulus of continuity of a function in terms of its Fourier coefficients - Zaderei, P. V.; Smal, ' B. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
In the integral metric, lower bounds are obtained for the best approximation and the modulus of continuity of a function in terms of its Fourier coefficients.